Analysis of Socioeconomic Factors Affecting Community Access to Public Health Services in Rural Areas - Mutmainnah Mutmainnah; Ince Annisah Adawiyah Arifin (Journal of Public Health Indonesian, 2025)
This study aims to analyze socioeconomic factors that affect rural communities ' access to public health services. The study used quantitative descriptive design with cross-sectional approach. The Data was collected through questionnaires from 190 respondents randomly selected from several villages. Data analysis was conducted using multiple linear regression to evaluate the relationship between family income, education level, employment status, and infrastructure access to health care access. The results showed that socioeconomic factors, such as family income, education level, and employment status, have a significant influence on the ability of rural communities to access health facilities. In addition, the distance to health facilities and the limited means of transport are the main barriers, creating access inequalities between people in rural and urban areas. The study recommends improving health infrastructure, health education programs, as well as subsidy policies to help low-income communities. The findings provide important insights for governments and relevant agencies to design inclusive and sustainable policies to improve the quality of health services in rural areas.